2010
DOI: 10.2478/v10019-010-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 905 MHz microwave radiation on colony growth of the yeast Saccharomyces cerevisiae strains FF18733, FF1481 and D7

Abstract: BackgroundThe aim of this study was to evaluate the effect of weak radiofrequency microwave (RF/MW) radiation emitted by mobile phones on colony growth of the yeast Saccharomyces cerevisiae.Materials and methodsS. cerevisiae strains FF18733 (wild-type), FF1481 (rad1 mutant) and D7 (commonly used to detect reciprocal and nonreciprocal mitotic recombinations) were exposed to a 905 MHz electromagnetic field that closely matched the Global System for Mobile Communication (GSM) pulse modulation signals for mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Growth limitation effects of RF-EMF have been mostly linked to changes in enzymatic activity and DNA damage caused by an increased level of reactive oxygen species (ROS) [ 15 , 16 ]. Moreover, Vrhovac et al ., have stated that colony growth reduction after exposure to 905 MHz RF-EMF generated by Global System for Mobile Communication (GSM) pulses (at a SAR of 0.12 W/kg) at least in a part was due to the impairment of DNA repairing mechanisms [ 9 ]. On the other hand, the exact mechanisms which RF-EMF stimulatestheproliferation of microorganisms are notfully known, yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth limitation effects of RF-EMF have been mostly linked to changes in enzymatic activity and DNA damage caused by an increased level of reactive oxygen species (ROS) [ 15 , 16 ]. Moreover, Vrhovac et al ., have stated that colony growth reduction after exposure to 905 MHz RF-EMF generated by Global System for Mobile Communication (GSM) pulses (at a SAR of 0.12 W/kg) at least in a part was due to the impairment of DNA repairing mechanisms [ 9 ]. On the other hand, the exact mechanisms which RF-EMF stimulatestheproliferation of microorganisms are notfully known, yet.…”
Section: Discussionmentioning
confidence: 99%
“…Kushwah et al ., showed that exposing Bacillus subtitles to low power microwave resulted in amylase and pectinase activity alteration along with an increase in exopolysaccharide production [ 7 ]. Depending on radiation period and intensity, microwave may either stimulate or suppress the fungal growth [ 8 , 9 ]. These results indicate that only if microorganisms are treated with microwave exposure at right frequency and duration, desirable changes in growth and metabolism would be induced.…”
Section: Introductionmentioning
confidence: 99%
“…Respiration activity, cell growth and glucose uptake were studied. 3. Regions (10-300) Hz, (10-100) Hz, (10-50) Hz and (50-100) Hz were investigated.…”
mentioning
confidence: 99%